2011
DOI: 10.1002/pros.21334
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prostate‐specific antigen (PSA) nadir and time to PSA nadir on disease progression in prostate cancer treated with androgen‐deprivation therapy

Abstract: We concluded that both PSA nadir and time to PSA nadir are significant predictors of disease progression for prostate cancer patients receiving ADT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 42 publications
3
81
2
Order By: Relevance
“…Numerous studies have demonstrated that Gleason scores and PSA levels are associated with the severity of clinical outcome. Huang et al (29) reported that the initial PSA level, a PSA nadir of ≥2 ng/ml and shorter time to PSA nadir were associated with disease progression. Furthermore, Chen et al (30) showed that initial level of PSA was a potential predictive factor for biochemical progression.…”
Section: A B Cmentioning
confidence: 99%
“…Numerous studies have demonstrated that Gleason scores and PSA levels are associated with the severity of clinical outcome. Huang et al (29) reported that the initial PSA level, a PSA nadir of ≥2 ng/ml and shorter time to PSA nadir were associated with disease progression. Furthermore, Chen et al (30) showed that initial level of PSA was a potential predictive factor for biochemical progression.…”
Section: A B Cmentioning
confidence: 99%
“…However, no correlation has been reported between primary PSA level and OS [11][12][13][14][15][16]. Furthermore, in studies including patients with locally-advanced and metastatic prostate cancer, the primary PSA level did not independently predict TTP nor OS [11,21,23]. These findings suggest the primary PSA level may not affect OS in patients with prostate cancer treated with ADT.…”
Section: Discussionmentioning
confidence: 90%
“…In this situation, it is important to precisely evaluate the clinical efficacy of ADT consisting of traditional maximum androgen blockade (MAB) at this time. There have been several reports of outcomes from patients with prostate cancer treated with ADT [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]; however, the number of studies, that reported outcomes in patients with bone metastatic prostate cancer treated primarily with MAB without any local treatment, is limited. Recently, outcomes of MAB as an initial treatment for patients with bone metastatic prostate cancer have been reported, in which the significant impact of PSA kinetics not on OS but on disease progression was demonstrated [16].…”
Section: Open Accessmentioning
confidence: 99%
“…[8][9][10][11][12][13] However, nadir PSA level and time to PSA nadir were unpredictable in initial diagnosis, and Gleason score was nonspecific for CRPC. It was known that androgen ablation provided a selective advantage to androgen-refractory cells that grow and eventually comprise most of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Although serum prostate specific antigen (PSA) has been considered the main indicator to assess the treatment response of ADT, it must be stressed that PSA level is not a reliable marker for CRPC and could not stand alone as a follow-up test. 2,[8][9][10] Patients with Gleason score 8 to 10 took a significantly shorter time to CRPC, [11][12][13] but the significant predictive value of high Gleason grade remains controversial. Therefore, it is very desirable to predict the prognosis of patients with primary PC using new technologies on clinical practice.…”
Section: Introductionmentioning
confidence: 99%